Phenotypic stability in elite pigeon pea (Cajanus cajan (L.) Mill.) genotypes using biplot models - Kishore, N Sandhya; Mohan Rao, P Jagan; Saritha, A; Neelima, G; Sandeep, S; Rao, P Madhukar; Chouhan , Sridhar; Lingaiah, N (Bangladesh Journal of Botany, 2022)
The yield stability of promisingpigeon pea genotypes across six locations was assessed using additive main effects and multiplicative interaction and Genotype plus genotype and environment interaction biplot models. The combined analysis of variance indicated that yield was significantly affected by genotypes, environments and genotype and environment interaction. The first two interaction principal componentsfrom the AMMI analysis accounted for 68.48% and from GGE accounted for 64.4% of variation due to GxE interaction. Both AMMI and GGE biplots identified G3 and G4 as most stable andG4 with the highest yield across six locations. The “What-won-where” biplot revealed that six environments fell into four sectors i.e.,E1and E2fell into one mega environment (ME 1), E3and E6another (ME 2), E4in one mega environment (ME 3) andE5 into another (ME 4). Environments E5and E1were most representative while E1could be regarded as least representative environment. Bangladesh J. Bot. 51(2): 371-380, 2022 (June)